Маркеры неосуществленного действия в болгарском и итальянском языках: союзы без да и senza (che) - Елена Юрьевна Иванова; Виктория Лазарева (MediAzioni, 2023)
The paper reviews Bulgarian conjunction bez da and Italian conjunction senza (che), introducing the subordinate clause with the relating to an unaccomplished action. The paper explores grammatical, syntactic, and semantic properties of these constructions in both languages. The similarity of semantic and functional potential of Bulgarian and Italian constructions as well as their intralingual specificity are shown.